1997
DOI: 10.1099/00222615-46-6-501
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation of Australian Isolates of Mycobacterium Tuberculosis by Pulsed-Field Gel Electrophoresis

Abstract: As part of an epidemiological study of tuberculosis in Australia, 84 isolates of Mycobacteriuin tuberculosis from patients were analysed by pulsed-field gel electrophoresis (PFGE). The isolates were genetically heterogeneous, with 66 different DNA banding patterns obtained following digestion of genomic DNA with Dral and 53 patterns with Xbal. When the results were compared with those previously obtained in restriction fragment length polymorphism analysis (RFLP), in 87% of cases the results with Dral were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This hypothesis was supported by the PGRS probe, since isolates from old patients were also related when they were subjected to this probe. Previous studies showed the PGRS probe to be a powerful tool that can differentiate between strains that lack the IS6110 sequence and those that contain a few copies of this genetic element (10,11). The numbers of IS6110 and PGRS copies in the isolates cultured from old patients in Tehran were higher than those cultured from refugees and immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was supported by the PGRS probe, since isolates from old patients were also related when they were subjected to this probe. Previous studies showed the PGRS probe to be a powerful tool that can differentiate between strains that lack the IS6110 sequence and those that contain a few copies of this genetic element (10,11). The numbers of IS6110 and PGRS copies in the isolates cultured from old patients in Tehran were higher than those cultured from refugees and immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…PFGE typing has successfully been used to differentiate between strains of M. tuberculosis (159), M. bovis (160), and M. bovis BCG (161). The reproducibility and discriminatory power of PFGE-based methods are high, although their use seems to be restricted to scientific or reference laboratories.…”
Section: Methods Based On Nonrepetitive Sequencesmentioning
confidence: 99%
“…PFGE is expensive and technically demanding, has a long turnover time (usually about 5 days), and, similarly to RFLP, requires large amounts of high-quality DNA. Moreover, discrimination between strains might not always be produced (159,162,163). The above-mentioned limitations discourage the use of PFGE for molecular epidemiological studies of MTBC infections.…”
Section: Methods Based On Nonrepetitive Sequencesmentioning
confidence: 99%
“…Finally, no standardized procedure for performing PFGE has yet been recommended. Despite these disadvantages, the PFGE typing was successfully used to differentiate between strains of M. tuberculosis [26], M. bovis [27], and M. bovis BCG [28]. However, the PFGE typing is rarely used in M. tuberculosis complex due to technical, time, and cost considerations, as mentioned above.…”
Section: Pulsed-field Gel Electrophoresis (Pfge)mentioning
confidence: 99%
“…However, the PFGE typing is rarely used in M. tuberculosis complex due to technical, time, and cost considerations, as mentioned above. Moreover, PFGE analysis does not always generate sufficient discrimination between the strains [26, 29, 30]. …”
Section: Pulsed-field Gel Electrophoresis (Pfge)mentioning
confidence: 99%